Size Optimization Design of 3T1R Parallel Mechanism based on Workspace - Liu Zhenkun; Luo Yufeng; Shi Zhixin; Xia Yongqiang; Xie Dongfu (Jixie chuandong)
An iterative rapid search algorithm of spherical coordinate variable step size is used to analyze the reachable workspace of a 3 T1 R parallel mechanism. The size of the mechanism is optimized by using the beetle antennae search algorithm. Firstly,the position of the mechanism is analyzed and its kinematic inverse solution is obtained. Then,an iterative rapid search algorithm with spherical coordinate variable step size is used to solve the reachable workspace of the 3 T1 R parallel mechanism. The workspace is measured by the size of workspace index,the influence of the structural parameters of the parallel mechanism on the working space volume is quantitatively analyzed. Finally,taking the maximum working space volume as the target,the structural parameters of the parallel mechanism are optimized by using the beetle antennae search algorithm,and the optimal value is obtained. The algorithm has fewer calculation steps and fast solution speed,which provides a theoretical basis for the practical application of such parallel mechanism.